CONTEXTUALIZING ALAN CLARKE’S SHORT MOVIE ‘ELEPHANT’: THE HISTORICAL APPROACH - Hotman Nasution; Tomi Arianto (eScience Humanity Journal, 2021)
The descriptive-qualitative paper purports an in-depth reading of the Trouble event depiction in Elephant movie by applying Greenblatt’s theory of Historicism. Elephant movie contains only 16 murders in a repeated and exact manners with no context and dialogue other than a sentence in the opening movie. New Historicism is expected to explain why the movie presents in such a way by correlating one to each other; the movie and the history. The data would be collected through observation and analyzed with content analyses method. The symmetrical positioning of the literary work and the history explains (1) how the massive censorship of media and the extremely strict rule in Northern Ireland shaped the idea of producing Elephant with covert relation to either political party in conflict (2) the absence of people who was responsible of the conflict explains the vagueness of who killed and who was killed, and (3) the erasure of characterization of the characters coincide with the cluelessness of who was the real victim.